ANALISIS PENANGGULANGAN BANJIR DI DAERAH KECAMATAN KARANGANYAR KABUPATEN DEMAK - Istianah, Istianah (NUCLEUS, 2024)
Flooding is a natural disaster caused by an increase in river discharge, as happened in February 2024 in Karanganyar Subdistrict due to the overflow of the Wulan River. This study aims to analyse flood discharge and provide recommendations for mitigation solutions. Using the Nakayasu Synthetic Unit Hydrograph (HSS) method, the 10-year return period flood discharge was found to be 3,829.424 m³/second, while the existing capacity of the Wulan River is 10,173.47 m³/second. To prevent future overflows, a ±1 metre high embankment elevation is required to be able to withstand a discharge of up to 13,882.51 m³/sec. This research provides a practical solution for flood control in the area.